Expanding our understanding of the relationship between nonsuicidal self‐injury and suicide attempts: The roles of emotion regulation self‐efficacy and the acquired capability for suicide. Issue 9 (30th March 2020) - Gratz, Kim L.; Spitzen, Tara L.; Tull, Matthew T.
Abstract: Objective: Although past literature has emphasized the role of acquired capability in the relationship between nonsuicidal self‐injury (NSSI) and suicide attempts, support for the indirect relationship of NSSI to suicide attempts through acquired capability is limited. Thus, research examining other factors that may underlie this relationship is needed. Across two studies, this research examined the indirect relationships of NSSI frequency to suicide attempts through both acquired capability and emotion regulation self‐efficacy (ERSE). Method: Two large samples of adults (one nationwide community sample and one clinical sample of patients with substance use disorders) completed questionnaires and/or interviews. Results: Results revealed significant indirect relationships of NSSI frequency to lifetime suicide attempts through ERSE, but not acquired capability, within both samples. Conclusions: Results highlight the relevance of ERSE to both suicide attempts and the NSSI‐suicide attempt relationship, and suggest the potential utility of interventions aimed at increasing ERSE among individuals with repeated NSSI.